Stakeholder Engagement Dan Komunikasi Krisis BP2MI Melalui Instagram Di Masa Krisis - Safinatul Wahidah (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2022)
This paper examined the stakeholders’ engagement and crisis communication of BP2MI through Instagram during the crisis. A qualitative descriptive approach with qualitative content analysis methods were conducted in this research. A total of 239 posts were collected manually from BP2MI's Instagram which has been verified during the crisis. The collected period starts from October 18th 2021 to December 10th 2021. The results show that stakeholder engagement tends to be passive engagement. Media type in image or photo formats attracts more stakeholder interaction than video format. Crisis-related content has a higher engagement rate than non-crisis-related content. BP2MI has consistently used adjusting information strategies and bolstering strategies as a combination. Keywords: stakeholder engagement, crisis communication, BP2MI, Instagram